Iron-silicon-aluminum magnetic powder core and preparation method and application thereof

Through multi-layer coating treatment of materials such as sol, phosphoric acid, nano-scale oxides and potassium water glass, the problems of poor insulation performance and low DC superposition performance of the ferrosilicon aluminum magnetic powder core are solved, and efficient insulating layer formation and performance improvement are achieved, and low loss, high superposition and high insulation ferrosilicon aluminum magnetic powder core is obtained.

CN119889900APending Publication Date: 2025-04-25HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311376113.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing ferrosilicon aluminum magnetic powder cores have problems such as poor insulation performance, high loss, poor DC superposition performance or poor environmental protection, especially in high DC and AC bias fields.

Method used

The first coating treatment is performed using sol, phosphoric acid, and nano-scale oxides, followed by the second and third coating treatments using potassium water glass and silicone resin to form a uniform and dense insulating layer to improve the insulating property and DC superposition performance of the magnetic powder core.

Benefits of technology

The resistivity, DC superposition performance and high temperature resistance of the ferrosilicon aluminum magnetic powder core are significantly improved, the strength and aging resistance of the magnetic powder core are improved, and the low loss, high superposition and high insulation ferrosilicon aluminum magnetic powder core is obtained, while ensuring environmental protection.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a Fe-Si-Al magnetic powder core and a preparation method and application thereof.The preparation method comprises the following steps that S1, sol, phosphoric acid, nanoscale oxide, a first solvent and a Fe-Si-Al powder matrix are mixed and then sequentially stirred and dried for the first time, and a first intermediate is obtained; s2, mixing potash water glass, a second solvent and the first intermediate, and sequentially stirring and secondarily drying to obtain a second intermediate; s3, mixing silicon resin, a silane coupling agent, a third solvent and the second intermediate, and sequentially performing stirring and third drying to obtain a third intermediate; s4, mixing the third intermediate and a release agent, and carrying out compression molding to obtain a prefabricated sample; and S5, carrying out heat treatment on the prefabricated sample in an inert atmosphere to obtain the Fe-Si-Al magnetic powder core. The Fe-Si-Al magnetic powder core prepared by the preparation method disclosed by the invention has excellent performances of low loss, high superposition and high insulativity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal soft magnetism, and in particular to a sendust magnetic powder core and a preparation method and application thereof. Background Art

[0002] With the rapid development of science and technology, the miniaturization and lightness of equipment have led to the miniaturization and high power density of electronic devices. Therefore, it is necessary to use magnetic powder core materials with high magnetic flux density, high DC bias performance, and high frequency and low loss. As a soft magnetic material with good high-frequency performance and low cost, Sendust magnetic powder core has been widely used in devices such as power factor corrector (PFC inductor), pulse flyback transformer and energy storage filter inductor, and its market demand is increasing. However, due to the relatively low saturation magnetic induction intensity of the material itself, the DC superposition performance of Sendust material is the lowest among all alloy magnetic powder cores, which seriously limits the application of Sendust material in high DC and AC bias fields. How to improve the DC superposition performance while reducing its loss has become a major challenge in today's research.

[0003] For example, the publication number CN103247403A discloses a method for preparing a metal soft magnetic powder core, which directly uses nano-oxide dispersion and sodium silicate powder to insulate and coat the metal magnetic powder, wherein 6.7wt% nano-MgO dispersion and 0.8% sodium silicate powder are used when coating the sendust magnetic powder, and finally a sendust magnetic core with an inductance of 58.5μH and a superposition of 100Oe of 36.5% is obtained. The nano-oxide dispersion has a good dispersion effect, but when it is mixed with water glass, it is easy to produce flocculent gel, which greatly reduces its effect as an insulating agent; and the nano-particles have poor adhesion to the magnetic powder, making it difficult to achieve uniform coating, and are easy to fall off during the pressing process, resulting in poor insulation performance of the metal soft magnetic powder core, high loss, and low superposition.

[0004] For example, the publication number CN101089108A ​​discloses an inorganic insulating binder for metal soft magnetic powder core and its preparation method. The inorganic insulating binder of the invention is a mixture of SiO2, Al2O3, ZrO2, mica powder and water. The suspended particles in the hydrate solution are close to the nanometer scale, and have the dual effects of insulation and bonding. The bonding effect can be enhanced during the heat treatment process to improve the stability of the powder core. Although the performance of the inorganic insulating binder is stable, the coating effect is not ideal, and it is difficult to achieve uniform and dense coating on the surface of the magnetic powder, which deteriorates the performance of the powder core.

[0005] For example, publication number CN114899002A discloses a method for preparing a low-loss, high-overlap FeSiAl metal powder core. The invention sequentially undergoes particle size screening, selective phosphating, particle size combination, etc., and finally obtains a magnetic permeability of about 60, 100Oe DC superposition of 58%, and a loss of 260mW / cm under 50k / 100mT conditions. 3 Although this method can improve the DC superposition performance of Sendust through selective phosphating of powder and particle size combination, the relatively simple insulation formula makes the improvement of DC superposition performance of magnetic powder core limited.

[0006] For example, the publication number CN115116689A discloses a low-loss and high DC bias magnetic powder core and its preparation method. The invention adopts an inorganic-organic multilayer coating and multiple coating insulation coating method to ensure the stability and uniformity of the insulation layer and reduce the adverse effect of the coating layer on the soft magnetic properties. The final magnetic permeability is 61-65, 100Oe DC superposition is 58%-62%, and the loss is 192-220mW / cm under 50k / 100mT. 3 Although this method can improve the DC superposition performance of Sendust to a certain extent, the use of chromic acid, which is harmful to the ecological environment and human health, limits its further use.

[0007] In summary, the coating process of the Sendust metal powder core in the prior art has the following problems: the coating effect is not ideal, and it is difficult to form a uniform and dense coating layer; or, in order to improve the coating effect, substances that are harmful to the ecological environment and the human body are used; which leads to the following problems in the Sendust metal powder core: poor insulation performance, high loss, poor DC superposition performance, or poor environmental protection. Summary of the invention

[0008] The main purpose of the present invention is to provide a sendust magnetic powder core and a preparation method and application thereof, so as to solve the problems of the sendust metal magnetic powder core in the prior art, such as poor insulation performance, high loss, poor DC superposition performance, or poor environmental protection.

[0009] In order to achieve the above object, according to one aspect of the present invention, a method for preparing a sendust magnetic powder core is provided, comprising the following steps: step S1, mixing a sol, phosphoric acid, a nano-sized oxide, a first solvent and a sendust powder matrix, stirring and first drying in sequence to obtain a first intermediate; the sol is selected from one or more of silica sol, aluminum sol, zirconium sol or silica aluminum sol; the nano-sized oxide is selected from one or more of SiO2, Al2O3 or ZrO2;

[0010] Step S2, mixing potassium water glass, the second solvent and the first intermediate, stirring and drying them in sequence to obtain a second intermediate;

[0011] Step S3, mixing the silicone resin, the silane coupling agent, the third solvent and the second intermediate, stirring and drying them in sequence to obtain a third intermediate;

[0012] Step S4, mixing the third intermediate and the mold release agent and performing compression molding to obtain a prefabricated sample;

[0013] Step S5, heat treating the prefabricated sample in an inert atmosphere to obtain a Sendust magnetic powder core.

[0014] Furthermore, the components of the Sendust powder matrix are 4.0-7.0wt% Al, 7.5-10wt% Si and the balance Fe.

[0015] Furthermore, the solid content of the sol is 10 to 40 wt %.

[0016] Furthermore, the particle size of the nano-scale oxide is ≤100 nm.

[0017] Furthermore, the first solvent is selected from water.

[0018] Furthermore, the first drying temperature is 60-150° C., and the time is 30-90 minutes.

[0019] Furthermore, the amount of sol used is 0.1-1 wt% of the weight of the Sendust powder matrix.

[0020] Furthermore, the amount of phosphoric acid used is 0.1-1 wt % of the weight of the sendust powder matrix.

[0021] Furthermore, the dosage of the nano-sized oxide is 0.1-1 wt% of the weight of the Sendust powder matrix.

[0022] Furthermore, after the first drying, after the second drying, after the third drying, and after the third intermediate and the demolding agent are mixed, the preparation method further includes the step of screening the material so that the particle size of the screened material is ≤80 mesh.

[0023] Furthermore, the pressing pressure is 1000-2200 MPa.

[0024] Furthermore, the amount of potassium water glass used is 0.3-2 wt % of the weight of the sendust powder matrix.

[0025] Furthermore, the modulus of potassium water glass is 2.3 to 3.3.

[0026] Furthermore, the second solvent is selected from water.

[0027] Furthermore, the second drying temperature is 60-150° C. and the time is 30-90 min.

[0028] Furthermore, the amount of silicone resin used is 0.3-2 wt % of the weight of the sendust powder matrix.

[0029] Furthermore, the amount of silane coupling agent used is 0.1-0.3 wt % of the weight of the sendust powder matrix.

[0030] Furthermore, the silicone resin is selected from methyl silicone resin and / or methylphenyl silicone resin.

[0031] Furthermore, the silane coupling agent is selected from one or more of KH-792, KH-550, KH-560 or KH-580.

[0032] Furthermore, the third solvent is selected from one or more of methanol, butanol, acetone or ethanol.

[0033] Furthermore, the temperature of the third drying is 60-100° C., and the time is 30-90 minutes.

[0034] Furthermore, the amount of the demoulding agent used is 0.1 to 0.6 wt % of the weight of the Sendust powder matrix.

[0035] Furthermore, the release agent is one or more of zinc stearate, aluminum stearate, talcum powder or mica powder.

[0036] Furthermore, the heat treatment temperature is 600-800° C., and the insulation time is 1-2 hours.

[0037] Furthermore, during the heat treatment process, the heating rate of the material from room temperature to the heat treatment temperature is 5 to 10°C / min.

[0038] In order to achieve the above object, according to one aspect of the present invention, a Sendust magnetic powder core is provided, which is prepared by the above-mentioned preparation method.

[0039] According to another aspect of the present invention, there is provided a use of the aforementioned Sendust magnetic powder core in an electronic device.

[0040] By applying the technical solution of the present invention, the present invention simultaneously uses organic and inorganic substances to insulate the sendust powder matrix, including a first coating treatment of sol, phosphoric acid, and nano-scale oxide, a second coating treatment of potassium water glass, and a third coating treatment of silicone resin and silane coupling agent. The entire coating layer is uniform and dense, which maximizes the resistivity, DC superposition, high temperature resistance and other properties of the sendust magnetic powder core. It also effectively improves the strength and aging resistance of the magnetic powder core, and finally obtains a sendust magnetic powder core with low loss, high superposition and high insulation. At the same time, the preparation method provided by the present invention does not use substances that harm the ecological environment, and the overall method is green, environmentally friendly and pollution-free. DETAILED DESCRIPTION

[0041] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0042] As described in the background technology section of this application, the Sendust metal powder core in the prior art has problems such as poor insulation performance, high loss, poor DC superposition performance, or poor environmental protection. In order to solve this problem, the present application provides a method for preparing a sendust metal magnetic powder core, comprising the following steps: step S1, mixing a sol, phosphoric acid, a nano-scale oxide, a first solvent and a sendust powder matrix, stirring and drying them in sequence to obtain a first intermediate; the sol is selected from one or more of silica sol, aluminum sol, zirconium sol or silica aluminum sol; the nano-scale oxide is selected from one or more of SiO2, Al2O3 or ZrO2; step S2, mixing potassium water glass, a second solvent and the first intermediate, stirring and drying them in sequence to obtain a second intermediate; step S3, mixing a silicone resin, a silane coupling agent, a third solvent and the second intermediate, stirring and drying them in sequence to obtain a third intermediate; step S4, mixing the third intermediate and a demolding agent, pressing and molding them to obtain a prefabricated sample; step S5, heat treating the prefabricated sample under an inert atmosphere to obtain a sendust magnetic powder core.

[0043] The present invention firstly uses sol, phosphoric acid and nano-scale oxide to perform a first coating treatment on the sendust powder matrix, so that the sendust powder matrix can still maintain the insulation effect between the powder particles after the subsequent high temperature (600-900°C) heat treatment, thereby improving the magnetic properties of the sendust magnetic powder core, making it have the characteristics of low loss rate and high magnetic permeability. In particular, in the process of coating the nano-scale oxide, the present application adds sol and phosphoric acid in a coordinated manner. The addition of phosphoric acid can modify the surface of the sendust powder matrix, and the Fe3(PO4)2 and FePO4 produced by the reaction with the sendust powder matrix will nucleate and grow on the surface of the magnetic powder. Since the growth direction of each crystal nucleus is inconsistent, the surface of the magnetic powder is uneven, which increases the roughness of the surface of the sendust powder matrix, thereby facilitating the attachment of nano-scale oxide particles, improving the compactness of the insulating coating layer, and making the performance of the nano-scale oxide more effectively exerted.

[0044] The sol of the present invention selects any one or more of silica sol, aluminum sol, zirconium sol or silica aluminum sol, which has the advantages of good dispersibility, high stability and high resistivity of colloidal particles, and is more conducive to improving the coating effect of nano-scale oxide particles. Since the ultrafine colloidal particles in the sol have a relatively large specific surface area and surface energy, the addition of the sol can play a good dispersing effect on the nano-oxide. In addition, the mesh structure pores generated by the agglomeration of countless micelles in the colloid allow the nano-oxide to be firmly adsorbed and more evenly attached to the surface of the sendustine powder matrix. At the same time, the -OH in the sol combines with the -OH sites on the surface of the acidified magnetic powder to form a reliable coating. When the water content of the sol evaporates, the Si-O, Al-O or Zr-O between the colloidal particles quickly combine, and together with the nano-oxide, it is firmly coated on the surface of the sendustine powder matrix to form a uniform insulating film, thereby improving the uniformity of the insulating coating layer and further improving the insulation of the sendustine magnetic powder core.

[0045] The present invention uses potassium water glass to perform a second coating treatment on the first intermediate. Potassium water glass has a high heat-resistant temperature and resistivity, and has low eddy current loss under high frequency, so it is an excellent insulating coating agent. When potassium water glass is used as the second insulating layer of the sendust powder matrix, it can not only further solidify the nano oxide of the first insulating layer, so that it is more firmly attached to the surface of the magnetic powder, but also effectively fill the gap between the nano oxide and the sendust powder matrix, so that the insulation effect of the sendust magnetic powder core is better, and the DC superposition performance of the sendust magnetic powder core is also improved and the loss is reduced.

[0046] The present invention adopts silicone resin and silane coupling agent to perform third coating treatment on the second intermediate. Silicone resin has super strong bonding property, can make the magnetic powder core have sufficient strength, and also has good weather resistance and flexibility, can reduce the problem of insulation layer falling off caused by molding pressure, and its hydrophobic property is also beneficial to the anti-aging of the magnetic core. Silane coupling agent contains two different active groups amino and ethoxy, can form a molecular bridge between high molecular polymer and inorganic matter, increase the bonding strength, and the organic coating of silicone resin and silane coupling agent makes the sendust metal magnetic powder core have better insulation layer protection, avoid the insulation layer from falling off, and the coating layer is more uniform and dense, improves the strength and anti-aging property of the sendust magnetic powder core, and then obtains the sendust magnetic powder core with low loss, high superposition and good insulation.

[0047] In summary, the present invention uses both organic and inorganic substances to insulate the sendust powder matrix, and the coating layer is uniform and dense, which maximizes the resistivity, DC superposition, high temperature resistance and other properties of the sendust magnetic powder core, and effectively improves the strength and aging resistance of the magnetic powder core, and finally obtains a sendust magnetic powder core with low loss, high superposition and high insulation. At the same time, the preparation method provided by the present invention does not use substances that harm the ecological environment, and the overall method is green, environmentally friendly and pollution-free.

[0048] It is further explained here that in step S1, the components of the sendust powder matrix are 4.0-7.0 wt% Al, 7.5-10 wt% Si and the balance Fe.

[0049] In an optional embodiment, the sendust powder matrix of the present invention can be prepared by the following method: a gas atomization method is used to prepare sendust powder with a particle size of ≤200 mesh, the composition of the sendust powder is 4.0-7.0wt% Al, 7.5-10wt% Si and the balance Fe, and the sendust powder is annealed under an inert atmosphere (preferably one or more of hydrogen, nitrogen or argon), the annealing temperature is 600-900°C, during the annealing process, the temperature is increased from room temperature to the annealing temperature at a heating rate of 5-10°C / min, and the insulation time is 1-2h to obtain the sendust powder matrix.

[0050] In order to further improve the nano-oxide coating effect, the solid content of the sol is preferably 10-40 wt%.

[0051] In a preferred embodiment, the particle size of the colloidal particles in the sol is ≤30nm, and the sol particles of this size have good dispersibility and can be filled in the gaps between the coarser nano-oxides to improve the integrity of the coating layer. Further preferably, the particle size of the colloidal particles in the sol is 5-15nm.

[0052] In order to further improve the dispersion performance of the nano-scale oxide and make the coating layer more uniform and dense, the particle size of the nano-scale oxide is ≤100 nm, and more preferably the particle size of the nano-scale oxide is 30±5 nm. Preferably, the first solvent is selected from water.

[0053] In order to allow the first solvent to fully evaporate, so that the sol, phosphoric acid and nano-scale oxides are more evenly and densely coated on the surface of the Sendust powder matrix, and thereby make the Sendust magnetic powder core have lower loss rate, higher magnetic permeability and better insulation, the first drying temperature is 60-150°C and the time is 30-90 minutes.

[0054] In order to further improve the nano-scale oxide coating effect and make the magnetic properties of the sendust magnetic powder core better, preferably in step S1, the amount of sol is 0.1-1wt% of the sendust powder matrix, for example, it can be 0.1wt%, 0.2wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt%. Preferably, the amount of phosphoric acid is 0.1-1wt% of the sendust powder matrix, for example, it can be 0.1wt%, 0.2wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt%. Preferably, the amount of nano-scale oxide is 0.1-1wt% of the sendust powder matrix, for example, it can be 0.1wt%, 0.2wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt%.

[0055] The present invention specifically designs the dosage ratio of sol, phosphoric acid and nano-scale oxide, and the three work synergistically with each other, so that the surface of the sendust powder matrix has a stable, uniform and dense nano-scale oxide coating layer, and then the sendust magnetic powder core with high magnetic constant, low loss and good insulation can be obtained. The dosage of sol is controlled within the range of 0.1-1wt%, so that the nano-scale oxide can be more uniformly and stably adsorbed and coated on the surface of the sendust powder matrix by the sol to form a uniform insulating film. However, too high a dosage of sol will lead to an increase in the viscosity of the solution, which is not conducive to the uniform dispersion of the nano-scale oxide, and the magnetic powder structure after phosphoric acid passivation is loose, and the insulating layer is easy to fall off during pressing. Too low a dosage will lead to the nano-scale oxide not being well dispersed, resulting in the nano-scale oxide coating layer being uniform and poor in density. Controlling the dosage of phosphoric acid within the range of 0.1-1wt% can better improve the roughness of the surface of the sendust powder matrix, facilitate the attachment of nano-scale oxide particles, and improve the density of the insulating coating layer. However, if the amount of phosphoric acid is too high, the magnetic permeability of the product will drop rapidly, the superposition loss will worsen, and the brittle phosphate will be prone to cracking during pressing. If the amount is too low, the roughness of the Sendust powder matrix will not be improved well.

[0056] In a preferred embodiment, after the first drying, the second drying, the third drying, and the mixing of the third intermediate and the release agent, the preparation method further includes the step of screening the material so that the particle size of the screened material is ≤80 mesh.

[0057] The present invention controls the particle size of the intermediates in each step to be ≤80 meshes, which is beneficial to the subsequent coating process, making the coating more uniform and dense, and sieving is performed after the third intermediate and the demolding agent are mixed, so that the particle size of the sendust magnetic powder core can be controlled to avoid the particle size of the sendust magnetic powder core being too large, resulting in a decrease in magnetic powder performance. The above operation is beneficial to the preparation of a sendust magnetic powder core with high magnetic permeability, low loss and good DC superposition performance.

[0058] In order to further obtain a sendust magnetic powder core with better magnetic properties, the pressing pressure is 1000-2200MPa. Too high a pressure will lead to a decrease in DC superposition performance and an increase in loss, while too low a pressure will lead to a significant decrease in magnetic permeability.

[0059] In order to further improve the potassium water glass coating effect and make the sendust magnetic powder core have a more uniform and dense coating layer, in step S2, the amount of potassium water glass is 0.3-2wt% of the sendust powder matrix. For example, it can be 0.3wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%. When the amount of potassium water glass is too high, the pressing density of the product will be reduced, the magnetic properties will deteriorate, and the reliability will be reduced. When the amount of potassium water glass is too low, the DC superposition performance of the sendust magnetic powder core will be reduced and the loss rate will be increased. Preferably, the modulus of potassium water glass is 2.3-3.3. Preferably, the second solvent is selected from water.

[0060] In order to further improve the uniformity and density of the potassium water glass coating layer, so as to make the sendust magnetic powder core have lower loss rate, higher DC superposition performance and better insulation, the second drying temperature is 60-150°C and the time is 30-90 minutes.

[0061] In order to further obtain a sendust magnetic powder core with better magnetic properties, in step S3, the amount of silicone resin is 0.3-2wt% of the sendust powder matrix. For example, it can be 0.3wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%. When the amount of silicone resin is too high, the fluidity of the powder will deteriorate, the product molding will be difficult, the glue will decompose violently during sintering, and the product will be easy to crack; if the amount is too low, the third insulating layer will be unevenly coated and the product reliability will be reduced. Preferably, the amount of silane coupling agent is 0.1-0.3wt% of the sendust powder matrix. For example, it can be 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%. When the amount of silane coupling agent is too high, the magnetic properties will be reduced; when the amount is too low, the connection between the second insulating layer and the third insulating layer will be weak, and the insulating layer will easily fall off.

[0062] In order to further improve the dispersion of silicone resin and silane coupling agent, the third solvent is selected from one or more of methanol, butanol, acetone or ethanol.

[0063] In order to further improve the magnetic properties of the sendust magnetic powder core, the silicone resin is selected from one or more of methyl silicone resin or methylphenyl silicone resin; preferably, the silane coupling agent is selected from one or more of KH-792, KH-550, KH-560 or KH-580. In some optional embodiments, the above KH-792, KH-550, KH-560 or KH-580 can be purchased from Yunsheng Chemical (Shandong) Co., Ltd.

[0064] In order to further improve the coating effect of silicone resin and silane coupling agent, and thus make the sendust magnetic powder core have better strength and aging resistance, the temperature of the third drying is 60-100°C and the time is 30-90 minutes.

[0065] In a preferred embodiment, in step S4, the amount of the demolding agent is 0.1-0.6wt% of the weight of the sendust powder matrix. For example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%. The present invention controls the demolding agent within the above range, which can reduce the residual rate of the pressed sendust magnetic powder product. Preferably, the demolding agent is one or more of zinc stearate, aluminum stearate, talcum powder or mica powder.

[0066] In a preferred embodiment, in step S5, the heat treatment temperature is 600-800°C and the holding time is 1-2h. The present invention limits the heat treatment temperature and time within the above range to make the sendust metal powder core have better strength and magnetic properties. When the temperature is too low, the strength of the sendust metal powder core will be poor and the performance will be low, but when the temperature is too high, the coating of the sendust metal powder core will be burned through, the insulation will be reduced, the loss will be increased, and the performance will deteriorate.

[0067] In order to improve the stability of heat treatment and make the magnetic properties of the Sendust metal powder core better, preferably during the heat treatment process, the heating rate of the material from room temperature to the heat treatment temperature is 5-10°C / min.

[0068] The present invention also provides a Sendust magnetic powder core, which is prepared by the above-mentioned Sendust magnetic powder core preparation method. Based on the above reasons, the Sendust magnetic powder core obtained by the preparation method of the present invention has better insulation performance, DC superposition performance and lower loss.

[0069] The present invention also provides an application of a Sendust magnetic powder core in an electronic device. Based on the above reasons, the Sendust magnetic powder core of the present invention has better DC superposition performance under lower loss conditions and has better performance when applied to electronic devices.

[0070] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0071] Example 1

[0072] The preparation method of the sendust magnetic powder core comprises the following steps:

[0073] Preparation of Sendust powder matrix: Sendust powder with a particle size of ≤200 mesh is placed in a nitrogen sintering furnace for annealing. The annealing temperature is 810°C. The temperature is raised by programmed heating at a rate of 5°C / min from room temperature to the annealing temperature. The temperature is kept at 810°C for 1h to obtain a Sendust powder matrix (wherein the Fe content is 85wt%, the Si content is 9wt%, and the Al content is 6wt%).

[0074] Preparation of Sendust magnetic powder core:

[0075] Step S1, first coating treatment: Aluminum sol (solid content of 20%, colloidal particle size range of 5-15nm), phosphoric acid, nano-scale SiO2 (particle size of 30±5nm) and water are mixed to form a mixture solution, the mixture solution is mixed with the sendust powder matrix and stirred evenly, and then the first drying is performed, the drying temperature is 120°C, the drying time is 90min, and the dried material is sieved to make the particle size of the sieved material ≤80 mesh, to obtain a first intermediate. Wherein, based on the weight of the sendust powder matrix as 100wt%, the amount of aluminum sol is 0.6wt%, the amount of phosphoric acid is 0.5wt%, the amount of nano-scale SiO2 is 0.2wt%, and the amount of water is 4wt%.

[0076] Step S2, second coating treatment: potassium water glass (modulus of 2.2), water, and the first intermediate are mixed and stirred evenly, and then dried for a second time at a drying temperature of 120° C. and a drying time of 90 min. The dried material is sieved to make the particle size of the sieved material ≤ 80 meshes to obtain a second intermediate. Wherein, based on the weight of the sendustine powder matrix as 100wt%, the amount of potassium water glass is 0.5wt%, and the amount of water is 4wt%.

[0077] Step S3, third coating treatment: methyl silicone resin (purchased from Hubei Longsheng Sihai New Materials Co., Ltd.), silane coupling agent KH-550 (purchased from Yunsheng Chemical (Shandong) Co., Ltd.), and acetone are mixed to form a mixture solution, the mixture solution is mixed with the second intermediate and stirred evenly, and then the third drying is performed, the drying temperature is 80°C, the drying time is 60min, and the dried material is sieved to make the particle size of the sieved material ≤80 mesh, to obtain the third intermediate. Wherein, based on the weight of the sendustine powder matrix as 100wt%, the amount of silicone resin is 0.5wt%, the amount of silane coupling agent is 0.2wt%, and the amount of acetone is 4wt%.

[0078] Step S4, compression molding: after mixing the third intermediate and the demoulding agent zinc stearate (based on the weight of the sendustine aluminum powder matrix as 100wt%, the amount of zinc stearate is 0.3wt%), the material is sieved so that the particle size of the sieved material is ≤80 mesh; and the sieved material is compressed and molded at 2000MPa to obtain a prefabricated sample magnetic ring;

[0079] Step S5, heat treatment: heat treat the prefabricated sample magnetic ring in a nitrogen atmosphere furnace at a temperature of 700°C, a heating rate of 5°C / min from room temperature to the heat treatment temperature, and a holding time of 1h to obtain a Sendust magnetic powder core.

[0080] Example 2

[0081] The only difference from Example 1 is that the aluminum sol is replaced by zirconium sol (solid content is 20%, and the particle size range of the colloidal particles is 5 to 15 nm).

[0082] Example 3

[0083] The only difference from Example 1 is that the aluminum sol is replaced by silica sol (solid content is 20%, and the particle size range of the colloidal particles is 5 to 15 nm).

[0084] Example 4

[0085] The only difference from Example 1 is that the aluminum sol is replaced by silica-alumina sol (the weight ratio of SiO2 / Al2O3 in the silica-alumina sol is 1:3, the solid content is 20%, and the particle size range of the colloidal particles is 5-15 nm).

[0086] Example 5

[0087] The only difference from Example 3 is that, based on 100wt% of the sendust powder matrix weight, the amount of silica sol used is 0.1wt%, the amount of phosphoric acid used is 0.1wt%, and the amount of nano-oxide used is 0.1wt%.

[0088] Example 6

[0089] The only difference from Example 3 is that, based on 100wt% of the sendust powder matrix weight, the amount of silica sol used is 1wt%, the amount of phosphoric acid used is 1wt%, and the amount of nano-oxide used is 1wt%.

[0090] Example 7

[0091] The only difference from Example 3 is that, based on 100wt% of the sendust powder matrix, the amount of potassium water glass used is 2wt%.

[0092] Example 8

[0093] The only difference from Example 3 is that the amount of silicone resin used is 2 wt %, based on 100 wt % of the sendust powder matrix.

[0094] Example 9

[0095] The only difference from Example 3 is that the amount of sol used is 2 wt %, based on 100 wt % of the sendust powder matrix.

[0096] Example 10

[0097] The only difference from Example 3 is that the amount of sol used is 0.05wt%, based on 100wt% of the sendust powder matrix.

[0098] Embodiment 11

[0099] The only difference from Example 3 is that the particle size of the colloidal particles in the sol is 60 to 150 nm.

[0100] Comparative Example 1

[0101] The only difference from Example 3 is that silica sol and phosphoric acid are not added in the first coating process of the preparation method of the sendust magnetic powder core in this comparative example.

[0102] Comparative Example 2

[0103] The only difference from Example 3 is that the preparation method of the Sendust magnetic powder core in this comparative example does not include silica sol, phosphoric acid, and nano-scale SiO2 raw materials, that is, the Sendust powder matrix does not undergo the first coating treatment of Example 3.

[0104] Comparative Example 3

[0105] The only difference from Example 3 is that the preparation method of the sendust magnetic powder core of this comparative example does not include potassium water glass raw material, that is, the sendust powder matrix does not undergo the second coating treatment of Example 3.

[0106] Comparative Example 4

[0107] The only difference from Example 3 is that the preparation method of the sendust magnetic powder core in this comparative example does not include silicone resin, silane coupling agent, and acetone raw materials, that is, the sendust powder matrix does not undergo the third coating treatment of Example 3.

[0108] Performance Testing

[0109] Magnetic permeability test method: Test instrument: CH3302 inductance tester Test frequency voltage: 100khz / 1V Test turns: 0.4mm 25Ts;

[0110] DC superposition test method: Test instrument: CH3302 inductance tester Test frequency voltage: 100khz / 1V Test turns: 0.4mm 25Ts Test current: 0A, 20A;

[0111] Loss test method: Test instrument: SY8218 power consumption tester Test conditions: 50khz / 100mT Test turns: 0.4mm 22×22Ts.

[0112] The Sendust magnetic powder cores prepared in the above examples and comparative examples were subjected to magnetic permeability, DC superposition (100 Oe) and loss tests (50 k / 100 mT). The test results are shown in Table 1.

[0113] Table 1

[0114] Magnetic permeability (H / m) DC superposition (%) <![CDATA[Loss (mW / cm 3 )]]> Example 1 62 61 212 Example 2 64 57 223 Example 3 60 66 187 Example 4 59 64 205 Example 5 70 52 235 Example 6 42 78 303 Example 7 49 73 273 Example 8 52 64 291 Example 9 51 71 233 Example 10 65 56 237 Embodiment 11 58 67 203 Comparative Example 1 72 49 266 Comparative Example 2 78 32 289 Comparative Example 3 67 55 206 Comparative Example 4 62 62 234

[0115] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a sendust magnetic powder core, characterized in that: The following steps are involved: Step S1, mixing a sol, phosphoric acid, a nano-sized oxide, a first solvent and a sendust powder matrix, stirring and drying them in sequence to obtain a first intermediate; the sol is selected from one or more of silica sol, alumina sol, zirconium sol or silica-alumina sol; the nano-sized oxide is selected from one or more of SiO2, Al2O3 or ZrO2; Step S2, mixing potassium water glass, a second solvent and the first intermediate, stirring and drying them in sequence to obtain a second intermediate; Step S3, mixing the silicone resin, the silane coupling agent, the third solvent and the second intermediate, stirring and drying them in sequence to obtain a third intermediate; Step S4, mixing the third intermediate and the mold release agent and performing compression molding to obtain a prefabricated sample; Step S5, heat treating the prefabricated sample in an inert atmosphere to obtain the Sendust magnetic powder core.

2. The method for preparing the Sendust magnetic powder core according to claim 1, characterized in that: In the step S1, the components of the sendust powder matrix are 4.0-7.0wt% Al, 7.5-10wt% Si and the balance Fe; Preferably, the solid content of the sol is 10 to 40 wt %; Preferably, the particle size of the colloidal particles in the colloid is ≤30 nm; Preferably, the particle size of the nano-scale oxide is ≤100 nm; Preferably, the first solvent is selected from water; Preferably, the temperature of the first drying is 60-150° C., and the time is 30-90 min.

3. The method for preparing the Sendust magnetic powder core according to claim 1 or 2, characterized in that: In the step S1, the amount of the sol is 0.1-1 wt% of the weight of the sendust powder matrix; Preferably, the amount of phosphoric acid is 0.1-1 wt% of the weight of the sendust powder matrix; Preferably, the amount of the nano-sized oxide is 0.1-1 wt % of the weight of the Sendust powder matrix.

4. The method for preparing a Sendust magnetic powder core according to any one of claims 1 to 3, characterized in that: After the first drying, after the second drying, after the second drying, after the third intermediate and the release agent are mixed, the preparation method further comprises the step of screening the material so that the particle size of the screened material is ≤80 mesh; Preferably, the pressing pressure is 1000-2200 MPa.

5. The method for preparing a Sendust magnetic powder core according to any one of claims 1 to 4, characterized in that: In the step S2, the amount of potassium water glass used is 0.3-2wt% of the weight of the sendust powder matrix; Preferably, the modulus of the potassium water glass is 2.3 to 3.3; Preferably, the second solvent is selected from water; Preferably, the second drying is performed at a temperature of 60 to 150° C. and for a time of 30 to 90 minutes.

6. The method for preparing a Sendust magnetic powder core according to any one of claims 1 to 5, characterized in that: In the step S3, the amount of the silicone resin is 0.3-2 wt% of the weight of the sendust powder matrix; Preferably, the amount of the silane coupling agent is 0.1-0.3 wt% of the weight of the sendust powder matrix; Preferably, the silicone resin is selected from methyl silicone resin and / or methylphenyl silicone resin; Preferably, the silane coupling agent is selected from one or more of KH-792, KH-550, KH-560 or KH-580; Preferably, the third solvent is selected from one or more of methanol, butanol, acetone or ethanol; Preferably, the third drying is performed at a temperature of 60 to 100° C. and for a time of 30 to 90 minutes.

7. The method for preparing a Sendust magnetic powder core according to any one of claims 1 to 6, characterized in that: In the step S4, the amount of the demoulding agent is 0.1-0.6 wt% of the weight of the sendust powder matrix; Preferably, the demoulding agent is one or more of zinc stearate, aluminum stearate, talc or mica powder.

8. The method for preparing a Sendust magnetic powder core according to any one of claims 1 to 7, characterized in that: In step S5, the heat treatment temperature is 600-800°C and the holding time is 1-2h; Preferably, during the heat treatment process, the heating rate of the material from room temperature to the heat treatment temperature is 5-10°C / min.

9. A Sendust magnetic powder core, characterized in that: The Sendust magnetic powder core is prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the Sendust magnetic powder core according to claim 9 in electronic devices.

Citation Information

Patent Citations

  • Inorganic insulating adhesive for soft magentic metal powder core andits prepn process

    CN101089108A

  • Preparation method of metal soft magnetic powder core

    CN103247403A

  • Preparation method of low-loss high-superposition Fe-Si-Al metal magnetic powder core

    CN114899002A

  • Low-loss and high-direct-current-bias magnetic powder core and preparation method thereof

    CN115116689A